(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of surgical management of urolithiasis in patients with horseshoe kidney using different minimally invasive techniques. Subjects and methods: Using a case series design, we described six patients with horseshoe kidney complicated by urolithiasis who were treated with various surgical interventions at E Hospital, Viet Duc University Hospital, and Saint Paul General Hospital from October 2019 to October 2025. Results: Six cases of urolithiasis in horseshoe kidneys were included, comprising five men and one woman, aged 33–79 years. All patients presented with flank pain and/or gross hematuria. Urinalysis predominantly revealed microscopic hematuria, while urine cultures were negative in all cases. Preoperative imaging demonstrated calculi located in the renal pelvis, calyces, or ureter, with variable stone burden and associated grade II–III hydronephrosis. The surgical procedures included percutaneous nephrolithotomy (PCNL), retrograde intrarenal surgery (RIRS), and ureteroscopy (URS). All patients achieved the predefined postoperative success criterion, defined as complete stone clearance or clinically insignificant residual fragments (<4 mm). Operative time ranged from 45 to 110 minutes. No intraoperative complications were observed. All postoperative complications were classified as Clavien–Dindo grade I. The mean postoperative hospital stay was 3–4 days. At the 1-month follow-up, all patients met the predefined criteria for surgical success, with improvement of hydronephrosis to grade I on ultrasonography and marked resolution of clinical symptoms. Conclusion: Minimally invasive treatment modalities, including percutaneous nephrolithotomy, flexible ureteroscopy, and ureteroscopic lithotripsy, has demonstrated promising preliminary outcomes in patients with horseshoe kidney.